Microplastics alter the functioning of marine microbial ecosystems - Daniel Montoya; Eugenio Rastelli; Raffaella Casotti; Vincenzo Manna; Anna Chiara Trano; Cecilia Balestra; Chiara Santinelli; Maria Saggiomo; Clementina Sansone; Cinzia Corinaldesi; Jose M. Montoya; Christophe Brunet (Ecology and Evolution)
Abstract Microplastics pervade ocean ecosystems. Despite their effects on individuals or populations are well documented, the consequences of microplastics on ecosystem functioning are still largely unknown. Here, we show how microplastics alter the structure and functioning of pelagic microbial ecosystems. Using experimental pelagic mesocosms, we found that microplastics indirectly affect marine productivity by changing the bacterial and phytoplankton assemblages. Specifically, the addition of microplastics increased phytoplankton biomass and shifted bacterial assemblages' composition. Such changes altered the interactions between heterotrophic and autotrophic microbes and the cycling of ammonia in the water column, which ultimately benefited photosynthetic efficiency. The effects of microplastics on marine productivity were consistent for different microplastic types. This study demonstrates that microplastics affect bacteria and phytoplankton communities and influence marine productivity, which ultimately alters the functioning of the whole ocean ecosystem.